STUDI KASUS KEMIRINGAN GEDUNG 4 LANTAI AKIBAT KEGAGALAN FONDASI DI PANGKAL PINANG - Orlando Orlando; Gregorius Sandjaja Sentosa (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2021)
Foundation is the lower structure of the building located below the ground that has the function to bear the load of the building. The building has been standing for ± 5 years and the slope of the building is ± 1-20. The authors analyzed soil bearing capacity, settlement and the slope of the building and the possibility of repairing the building for reuse. In 1 pile cap there are 4 bore piles with a depth of 6m-12m, because the pile cap data is not obtained then the size and thickness is assumed and the soil data used is secondary data without lab data derived from soil data in locations adjacent to the building site that is ±100m from the building site. After the analysis, soil bearing capacity is not strong to bear the dead load of the building when using a foundation with a depth of 6m-12m, there is a possibility that the foundation used is not suitable and there is a reduction in the load of the building due to the presence of other buildings that are adjacent to the building in the analysis resulting in a considerable decrease and slope of the building.Fondasi adalah struktur bagian bawah bangunan yang terletak di bawah permukaan tanah yang mempunyai fungsi memikul beban bangunan. Bangunan ini sudah berdiri selama ± 5 tahun dan kemiringan bangunan sebesar ± 1-20. Penulis menganalisis daya dukung tanah, penurunan tanah dan kemiringan bangunan dan kemungkinan memperbaiki bangunan agar dapat digunakan kembali. Pada 1 pile cap terdapat 4 buah bore pile dengan kedalaman 6m–12m, karena data pile cap tidak diperoleh maka ukuran dan ketebalannya diasumsikan dan data tanah yang digunakan adalah data sekunder tanpa data lab yang berasal dari data tanah di lokasi berdekatan dengan lokasi bangunan yang berjarak ±100m dari lokasi bangunan. Setelah di analisis, daya dukung tanah tidak kuat untuk menahan beban mati bangunan bila menggunakan fondasi dengan kedalaman 6m–12m dan ada kemungkinan fondasi yang digunakan tidak sesuai dan terjadi reduksi beban bangunan karena adanya bangunan lain yang berdempetan dengan bangunan yang di analisis sehingga mengakibatkan penurunan dan kemiringan bangunan yang cukup besar.